2020
DOI: 10.34172/apb.2020.059
|View full text |Cite
|
Sign up to set email alerts
|

Non-Classical Effects of the cAMP Accumulation Activators In Vivo

Abstract: Purpose : Wound-healing dipyridamole- and papaverine-based aerosols (D1/D2) as activators of the accumulation of cyclic adenosine monophosphate are promising drugs that can accelerate wound healing in wound processes of various origins. Methods: 128 rats were used in the study, including 38 in a pharmacological experiment on a model of stencil wounds and 90 in an experiment that studied the effect of spray on the number of CD34 cells in the blood of rats with chemically induced immunodeficiency. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…[ 28 ] Another study showcased the ability of topically applied endogenous stem cells to accelerate wound healing significantly in a diabetic rat model. [ 29 ] In a study by Martynov et al,[ 9 ] a 4×1 cm wound was created, and aerosol forms of papaverine and dipyridamole, another phosphodiesterase inhibitor, were investigated for their effects on wound healing at various time points. The results confirmed the superiority of papaverine and dipyridamole over dexpanthenol in terms of epithelialization, indicating their positive effect on wound healing and pluripotent CD34 cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] Another study showcased the ability of topically applied endogenous stem cells to accelerate wound healing significantly in a diabetic rat model. [ 29 ] In a study by Martynov et al,[ 9 ] a 4×1 cm wound was created, and aerosol forms of papaverine and dipyridamole, another phosphodiesterase inhibitor, were investigated for their effects on wound healing at various time points. The results confirmed the superiority of papaverine and dipyridamole over dexpanthenol in terms of epithelialization, indicating their positive effect on wound healing and pluripotent CD34 cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Papaverine, an opioid analog possessing myorelaxant and vasodilator effects on vascular smooth muscles, finds application in treating ischemia caused by spasms in the heart, brain, and peripheral blood vessels. [ 8 ] While a study reported that the aerosol form of papaverine accelerates wound healing and stimulates pluripotent CD34 cells,[ 9 ] another study demonstrated its application in a cream form on seven skin flaps, resulting in increased flap survival. [ 10 ] However, no prior research has explored the influence of papaverine on tendon healing.…”
Section: Introductionmentioning
confidence: 99%
“…Among intracellular messengers, cAMP and cGMP play pivotal roles in numerous biological processes, including visceral motility, reproduction, immune and inflammatory responses, vascular resistance, and cardiac output [8]. Intracellular levels of these second messengers are intricately regulated by the balance between synthesizing enzymes such as adenylate cyclase and guanylate cyclase and catabolic enzymes like phosphodiesterase enzymes (PDEs) [9].…”
Section: Introductionmentioning
confidence: 99%